Analisis Hate Comment Bagi Pengguna Platfrom Instagram Terhadap Kepercayaan Diri Mahasiswa FIS UINSU Stambuk 2021 - Syahla Hidayah; Yulia Permata Sari; Heny Anggreni Butar-Butar; M. Nur Badawani Siregar; Melisa Naibaho; Adnan Hasmuri Siregar; Sandy Yudha (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
This study aims to analyze the impact of hate comments on Instagram on the self-confidence of students from the Faculty of Social Sciences (FIS) at Universitas Islam Negeri Sumatera Utara (UINSU), class of 2021. Using a descriptive qualitative method, the research identifies psychological impacts experienced by students, such as anxiety, stress, and low self-esteem. The study also highlights strategies that students can employ to mitigate these impacts, including digital ethics education, digital literacy, and social support. The findings reveal that hate comments affect not only individual psychological conditions but also their social relationships. To address this issue, a holistic approach is required, including enhancing digital literacy and implementing protective policies on social media platforms.